2021
DOI: 10.1167/iovs.62.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Is Characterized by a Cold, CD8+ Cell Poor, PD-L1− Microenvironment, Which Turns Into Hot, CD8+ Cell Rich, PD-L1+ After Chemotherapy

Abstract: PURPOSE.To investigate the impact of chemotherapy (CHT) on human retinoblastoma (RB) tumor microenvironment (TME).CASES AND METHODS. Ninety-four RBs were studied, including 44 primary RBs treated by upfront surgery (Group 1) and 50 primary RBs enucleated after CHT (CHT), either intraarterial (IAC; Group 2, 33 cases) or systemic (S-CHT; Group 3, 17 cases). Conventional and multiplexed immunohistochemistry were performed to make quantitative comparisons among the three groups, for the following parameters: tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
2
8
2
Order By: Relevance
“…We observed that previous treatments did not modify the M2‐like polarized CD163 + environment of retinoblastoma, which is in contrast with a recent study of the retinoblastoma immune environment by Miracco et al [8]. They reported a significantly higher number of CD163 + M2‐like TAMs in previously treated human retinoblastoma eyes, compared to eyes enucleated without previous treatment [8].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We observed that previous treatments did not modify the M2‐like polarized CD163 + environment of retinoblastoma, which is in contrast with a recent study of the retinoblastoma immune environment by Miracco et al [8]. They reported a significantly higher number of CD163 + M2‐like TAMs in previously treated human retinoblastoma eyes, compared to eyes enucleated without previous treatment [8].…”
Section: Discussioncontrasting
confidence: 99%
“…Because IFN‐γ‐secreting cells, and specifically CD8 + lymphocytes, were moderately abundant in a high proportion of the retinoblastoma samples, we propose that tumor microenvironment inhibits such CD8 + cells, leading to a decreased level of IFN‐γ secretion [41]. The work by Miracco et al , in contrast, suggests that chemotherapy treatments induce a proinflammatory environment, leading to higher expression of PD‐L1 [8], but our results and others do not confirm their observation [9]. We suggest that M2‐like TAMs and Tregs suppress the activity of CD4 + and CD8 + TILs in retinoblastomas, because they inhibit the production of several proinflammatory cytokines such as IFN‐γ and IL‐2 [42].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a few lymphocytes, particularly T cells, in RB. This was consistent with recent studies also showing the absence of CD8+ cells, including T cells, B cells, in RB [ 55 ]. These results suggested that RB has relatively poor immunogenicity compared with most of tumors, which may contribute to the poor efficacy of immunotherapy in RB.…”
Section: Discussionsupporting
confidence: 94%
“…Targeting cancer stem cells have been recognized as an effective strategy for cancer therapy [2]. Retinoblastoma is the most common eye tumor in children that develops from the immature cells of retina [3]; the incidence of this disease is 1 in 15,000-20,000 live births and the median age at rst diagnosis is two years [4]. So far, non-invasive therapeutic strategies for retinoblastoma are limited; current therapeutic methods, including surgery (enucleation) and radiation, usually results in blindness and inactive treatment causes it life-threatening [5].…”
Section: Introductionmentioning
confidence: 99%